دور المنظمة المتعلمة على تمكين العاملين من وجهة نظر الموظفين في بعض الجامعات الجزائرية - سلام, عبد الرزاق; ختيري, وهيبة; بوعلاقة, نورة (University of eloued - جامعة الوادي, 2021)
هدفت الدراسة إلى التعرف، على أثر توافر خصائص المنظمة المتعلمة على تمكين العاملين من وجهة نظر الموظفين في بعض الجامعات الجزائرية، حيث تم صياغة الاستبيان من جزئيين، الجزء الأول يتضمن البيانات الشخصية المتعلقة بالموظفين، والجزء الثاني يتضمن أبعاد محور خصائص المنظمة المتعلمة يتكون من سبعة أبعاد يشمل 34 عبارة، ومحور تمكين العاملين يتضمن ثلاثة أبعاد يشمل 14 عبارة، واشتمل الاستبيان ككل على 48 عبارة، موجهة لعينة تتكون من 216 مفردة من الموظفين في بعض الجامعات الجزائرية. خلصت الدراسة في إطارها التطبيقي، إلى توفر خصائص المنظمة المتعلمة بشكل متوسط وعالي، وقدر المتوسط الحسابي للمحور ككل بـــــ 3,38 بدرجة موافقة متوسطة، كما جاء مستوى تمكين العاملين بدرجات متوسطة وعالية وقدر المتوسط الحسابي للمحور ككل بـــ 3,52 بدرجة موافقة عالية، كما توصلت الدراسة إلى وجود أثر للخصائص المنظمة المتعلمة على تمكين العاملين، في جميع أبعاده امتلاك المعرفة والمعلومات الاستقلالية والحرية والعمل الجماعي عند درجة معنوية 0.05 ومنه يمكن اعتبار الجامعات الجزائرية محل الدراسة تتبنى مفهوم المنظمة المتعلمة وتسعى إلى تمكين العاملين ولها القدرة على التكيف والتغير المستمر The study aimed at identifying The impact of the availability of the characteristics of the learning organization to Empowering Employees, from the point of view of employees in some Algerian universities. The questionnaire was composed of two parts. The first part includes the personal data related to the employees. The second part includes the axis dimensions of the characteristics of Learning Organization composing of seven dimensions including 34 statements, And the staff empowerment axis includes three dimensions of 14 statements. The questionnaire as a whole contains 48 statements, targeting a sample of 216 staff members in some Algerian universities. The study concluded that the average characteristics of the learning organization were medium and high, The arithmetic mean of the axis as a whole was 3.38 with medium approval rate. The level of medium and high Empowerment was high and the median mean of the axis was 3.52 with high approval. The study found a trace of the organization's learned characteristics on all dimensions of empowerment of workers, possession of knowledge and information independence, freedom and teamwork at a significant level of 0.05, from which Algerian universities can be regarded as adopting the concept of an educated organization and seeking to empower workers
The Role of learning Organisation to Empowering Employees, frome the point of view of Employees in some Algerian universitie
مقال
Keywords: المنظمة ، المنظمة المتعلمة، التمكين، الجامعات الجزائرية; The organization, the educated organization, empowerment, Algerian universities